2008
DOI: 10.1093/ndt/gfm908
|View full text |Cite
|
Sign up to set email alerts
|

Costs and outcomes of acute kidney injury (AKI) following cardiac surgery

Abstract: Background. Acute kidney injury (AKI) is a recognized complication of cardiac surgery; however, the variability in costs and outcomes reported are due, in part, to different criteria for diagnosing and classifying AKI. We determined costs, resource use and mortality rate of patients. We used the serum creatinine component of the RIFLE system to classify AKI. Methods. A retrospective cohort study was conducted from the electronic data repository at the University of Pittsburgh Medical Center of patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
214
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(238 citation statements)
references
References 21 publications
10
214
0
8
Order By: Relevance
“…For example, patients admitted to the hospital with community-acquired pneumonia have a 90-day mortality rate of 5% that increases to 10% in the setting of AKI (37). Similarly, hospital mortality after routine cardiothoracic surgery is generally low, at less than 2%, but increases to 11% in the setting of AKI (38). When studies in patients with AKI are being planned, it is critical to accurately assess the natural history of the diseases in the population with AKI and to integrate this knowledge with potential side effects of the drug or intervention to be studied.…”
Section: Considerations Regarding Adverse Events In Pilot and Feasibimentioning
confidence: 99%
“…For example, patients admitted to the hospital with community-acquired pneumonia have a 90-day mortality rate of 5% that increases to 10% in the setting of AKI (37). Similarly, hospital mortality after routine cardiothoracic surgery is generally low, at less than 2%, but increases to 11% in the setting of AKI (38). When studies in patients with AKI are being planned, it is critical to accurately assess the natural history of the diseases in the population with AKI and to integrate this knowledge with potential side effects of the drug or intervention to be studied.…”
Section: Considerations Regarding Adverse Events In Pilot and Feasibimentioning
confidence: 99%
“…Cardiac‐surgery–associated acute kidney injury (AKI) results in high resource utilization, in‐hospital mortality, permanent loss of renal function, and poor long‐term survival 1, 2, 3, 4. Patients undergoing cardiac surgery procedures performed with cardiopulmonary bypass (CPB; on‐pump) have a high risk of developing AKI 5…”
Section: Introductionmentioning
confidence: 99%
“…3,4 These definitions have aided in ascertainment of the true incidence of AKI after cardiac surgery and shown that AKI, regardless of severity or stage, is associated with longer length of intensive care unit (ICU) and hospital stay, increased cost of hospitalization, and increased patient mortality. 5,6 In recent years, several studies have shown that novel biomarkers can detect acute tubular injury earlier than serum creatinine in the setting of AKI. [7][8][9][10][11] Despite attempts to select patients at high risk for severe AKI, the majority of patients in these prospective studies do not develop clinical AKI.…”
mentioning
confidence: 99%